Association between sperm mitochondrial DNA copy number and deletion rate and industrial air pollution dynamics - Vozdova, Miluse; Kubickova, Svatava; Kopecka, Vera; Sipek, Jaroslav; Rubes, Jiri (Scientific reports, 2022)
The effects of air pollution on men's reproductive health can be monitored by evaluating semen quality and sperm DNA damage. We used real-time PCR to analyse the effects of air pollution on sperm mitochondrial DNA copy number (mtDNAcn) and deletion (mtDNAdel) rates in semen samples collected from 54 men in two seasons with different levels of industrial and traffic air pollution. MtDNAdel rates were significantly higher following the high exposure period and were positively correlated with mtDNAcn. However, we did not find any difference in mtDNAcn between the two seasons. MtDNAcn was positively correlated with the DNA fragmentation index and the rates of sperm with chromatin condensation defects, previously assessed by sperm chromatin structure assay, and negatively correlated with sperm concentration, progressive motility, viability, and normal morphology. This indicates that mtDNAcn is more closely associated with male fertility than mtDNAdel rates. In contrast, mtDNAdel might be a more sensitive biomarker of air pollution exposure in urban industrial environments.
Keywords: analýza spermatu; Sperm Motility; variabilita počtu kopií segmentů DNA; Chromatin; DNA, Mitochondrial; Spermatozoa; znečištění ovzduší; spermie; Humans; motilita spermií; mužské pohlaví; chromatin; lidé; Air Pollution; DNA Copy Number Variations; Male; mitochondriální DNA; Semen Analysis